Vliv věku, alkoholové intoxikace a charakteru poranění mozku na prognózu operovaných zraněných s kraniocerebrálním poraněním - Chrastina, J; Hrabovský, D; Ríha, I; Steinerová, K; Novák, Z (Rozhledy v chirurgii, 2013)
INTRODUCTION: Advanced age is reported to be an important negative prognostic factor for the final functional outcome in patients after craniocerebral injury. Worse prognosis can also be expected in the presence of significant brain contusion, requiring surgical treatment because of expansive behaviour. Definite adverse influence of alcohol intoxication at the time of injury has not been proven by current literature data. The aim of the study is to analyse the importance of the above mentioned factors for the treatment outcome in patients operated on for craniocerebral injury. MATERIAL AND METHODS: In the group of 246 patients with craniocerebral injury operated on between 2007 and 2011, the authors focused on the influence of age (145 patients < 60 years, 101 patients > 60 years), alcohol intoxication at the moment of injury (blood alcohol level over 0.1% based mainly on serum osmolarity plus clinical signs of alcohol intoxication) and the presence of brain contusion requiring surgical decompression on the final clinical outcome (using the Glasgow Outcome Scale). RESULTS: 54.1% of patients under 60 years of age were alcohol-intoxicated at the moment of injury. The incidence of alcohol intoxication in patients older than 60 years was 35.7%. The incidence of expansive brain contusions requiring surgical decompression was higher in patients older than 60 years and patients with alcohol intoxication. Statistical analysis of prognosis as related to age has shown significantly worse prognosis in patients older than 60 years. The difference was also significant in the subgroup of non-intoxicated patients. Statistical analysis did not show worse prognosis in alcohol-intoxicated patients. The presence of significant contusions influenced the injury prognosis only in patients younger than 60 years. CONCLUSION: The impact of age on the final treatment outcome in patients with craniocerebral injury was proven. The study did not show significant deleterious effect of alcohol intoxication at the time of injury on the final outcome.
Keywords: Young Adult; Male; mladý dospělý; prognóza; poranění mozku; Brain Injuries; otrava alkoholem; Adult; Craniocerebral Trauma; Age Factors; Aged; dospělí; mužské pohlaví; senioři; senioři nad 80 let; lidé; ženské pohlaví; kraniocerebrální traumata; Humans; věkové faktory; Aged, 80 and over; Prognosis; Alcoholic Intoxication; Female; lidé středního věku; Middle Aged